Assessment of Audit Activities in the Public Administration with a Focus on the Types of Audits: Practice in the Public Sector of the V4 Countries - Hudáková Stašová, Lenka (Public Finance Quarterly, 2022)
This paper focuses on audits of public administrations performed by Supreme Audit Offices (SAO). The aim of the paper is to assess the performance of audit activities by the highest audit institutions in the Visegrad Four (V4) countries with a focus on the types of audits performed (compliance audits, performance audits, financial audits) in the period of 2005-2020. Pearson’s correlation coefficient and Spearman’s correlation coefficient were used to test the set hypotheses. The study focuses on the relationships between the number of audits performed (especially compliance audits and performance audits) and the volume of audit findings, recommendations and actions. Compliance audits predominate in the Slovak Republic and Hungary. However, the current trend is to gradually increase the share of performance audits. Most performance audits were carried out in the Czech Republic. The analysis found a statistically significant relationship between the number of performance audits performed and the number of auditors’ recommendations in Poland and Hungary. In addition there is a statistically significant relationship between the number of performance audits performed and the number of audit findings in Poland and the Czech Republic.